TECHNICAL ANALYSIS AND FEASIBILITY OF PURSE SEINE FISHING FISHERY BUSINESS IN THE SIBOLGA ARCHIPELAGO, NORTH SUMATERA PROVINCE - Juliana Normauli Sinaga; Pareng Rengi; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in July-August 2019 at the Sibolga Nusantara Fisheries Port, North Sumatra Province. The purpose of this study is to determine the technical aspects of purse seine and analyze the feasibility of purse seine fishing. The method used in this study is a survey method. Primary data collection is done by direct interviews with fishermen and business owners who use purse seine. The sample used in this study was 5 ships with different GT sizes. From the results of trawl ring construction research consists of upper ris rope, lower ris rope, wings, body, pouches, slag, buoy, ballast and wrinkle rope. The results of the business feasibility analysis show that the NPV value for 29 GT vessels is Rp.125.236.270, 50 GT vessels is Rp.491.248.469, 77 GT ships is Rp.732.783.336, 98 GT ships is Rp.1.106.912.823, and 128 GT vessels totaling Rp.1.055.826.712, BCR value for ships 29 GT 1.3, 50 GT 1.0 vessels, 77 GT 1.0 vessels, 98 GT 2.0 vessels, and 128 GT 1.0 vessels, FRR value for ships 29 GT of 19%, 50 GT of 39%, 77 GT of 36%, 98 GT of 44%, and 128 GT of 26% and PP value for 29 GT 5 years 3 months, 50 GT ships 2 years 6 months, 77 GT ships 2 years 8 months, 98 GT ships 2 year 3 months, and 128 GT ships 3 years 8 months. Therefore, it can be concluded that the fishing effort is feasible to be run and developed.Keywords: Technical Analysis; Financial Analysis; Trawl fishing gear